Pengaruh Environmental Awareness , Green Product Features, Green Product Price, Green Product Promotion Terhadap Keputusan Pembelian Konsumen The Body Shop Di DKI Jakarta - Puspasari, Lidia; Putri Milenia, Dinda (Journal of Economics and Business UBS, 2022)
The body shop is one of the brand cosmetics that subbed the system green marketing. The body shop itself was founded by Anita roddick on March 27, 1976 in kensington garden, Brighton, England. The body shop's basic eco-friendly principle is born of the ide-the idea of reusing, replenishing, and recycling what they can regenerate. The body shop always USES natural raw materials or prevents the use-the ones that cannot be recycled. Green marketing as an environmentally-based marketing agent, can promote environmental awereness, green product features, green product price, and green product product. The study aims to identify environmental awereness, green product features, green product price, and green product transactions against the body shop decision in dki dki. The population in this study is the general public in dki Jakarta. The sample in this study was taken using an purposive sampling with a sample number of 100 people.. The data-collection technique USES a questionnaire that has been tested for its validity and realification. Whereas the collection of data consists of valiance tests and religious tests. Hypothetical tests made up of regression tests, tests of F, tests of t, classic assumptions test, and determinan coefficient test (R2). Research indicates that environmental awereness may have a positive and significant impact on purchasing decisions, green product features a positive and significant impact on purchasing decisions, as well as those of what is now called new product. The four above variables aimed at sharing or simultaneously at the decision to buy the body shop in DKI Jakarta.